The Impact of Semantic Web and Ontology to Improve E-government Services: A Systematic Review - Altahir, Badraldeen Hassan; Karrar, Abdelrahman Elsharif; Mohmmed, Shazali Siddig (IAES Indonesian Section, 2023)
The semantic web and ontology are extensions of the World Wide Web that aim to make data more interconnected and machine-readable. This systematic review examined researched publications published between 2018 and 2023 and indexed in Google Scholar and Science Direct. 23 records were chosen and classified into six groups: information and retrieval, knowledge archiving, interoperability, enhancing public and employee services, barriers to ontology application, and use of ontologies to apply the regulations. This study explored the semantic web and ontology used to enhance e-government services. It found that improving ontology for searched and information retrieval processes could help computers retrieve accurate results, improve interoperability and integration, and provide a knowledge base for terms used in building databases and applications. However, more research is needed to effectively integrate ontology into existing systems and extend these approaches to real-world contexts. Future research should focus on presenting an applied model of e-government technology and conducting continuous evaluations.